Development of a Solid Formulation Containing a Microemulsion of a Novel Artemisia Extract with Nematocidal Activity for Oral Administration - Ines Perez-Roman; Filip Kiekens; Damian Cordoba-Diaz; Juan Jose Garcia-Rodriguez; Manuel Cordoba-Diaz (MDPI AG, 2020)
Background: Intestinal nematode infections are usually treated with benzimidazole drugs, but the emergence of resistance to these drugs has led to an increasing demand of new anthelmintic strategies. A new microemulsion formulation (ME) consisting of an Artemisia absinthium extract with proven nematocidal efficacy was previously developed. The aim of our study is to implement a D-optimal mixture design methodology to increase the amount of a silica material (loaded with this ME) in a tablet formulation, considering its tensile strength and disintegration time. Methods: 16 experiments or combinations of the 6 tablet components (loaded silica, microcrystalline cellulose, polyvinylpyrrolidone, croscarmellose, Syloid® 244 FP and magnesium stearate) were assessed. Tensile strength and disintegration time models were developed, and an optimization process was carried out. Results: Tensile strength was improved by increasing the polyvinylpyrrolidone content, while croscarmellose decreased the disintegration time. The optimized powder mixture contains 49.7% w/w of the loaded silica material. A compression force of 12 kN was applied to the powder mixture to form tablets with a tensile strength of 2.0 MPa and a disintegration time of 3.8 min. Conclusions: Our results show that D-optimal mixture designs provide a promising approach to formulate liquid-loaded silica materials.